Post-fertilization expression of FLOWERING LOCUS T suppresses reproductive reversion - Liu, Liangyu; Farrona, Sara; Klemme, Sonja; Turck, Franziska K. (Frontiers in Plant Science, 2014)
FLOWERING LOCUS T (FT) encodes a systemic signal communicating the perception of long day photoperiod from leaves to the shoot apex to induce the floral transition. Transient expression of FT in the phloem companion cells of rosette leaves for one to several days was previously shown to be sufficient to commit plants to flowering. Here we show that that partial commitment results in pleiotropic inflorescence meristem reversion phenotypes. FT expression is much stronger in organs formed after the floral transition such as cauline leaves, sepals and developing siliques. We show that expression of FT and its paralog TWIN SISTER OF FT (TSF) after the floral transition plays a role in inflorescence meristem stabilization even if plants flower very late in development. CONSTANS (CO), the major activator of FT, is not required to prevent late reproductive reversion. The requirement for FT is temporal since reproductive reversion to a vegetative state occurs only in recently formed inflorescence meristems. Unlike for the expression of FT in leaves, neither the distal putative FT enhancer nor long-day photoperiod are required for FT expression in developing siliques. Expression of FT in developing siliques and their supporting stems is sufficient to stabilize flowering during the sensitive developmental window indicating that fruit generated FT participates in inflorescence stabilization.